Kaunayen chicken – a new indigenous germplasm from Manipur - VIJ, P K; TANTIA, M S; SINGH, TH RANADHIR (The Indian Journal of Animal Sciences, 2016)
Kaunayen is an indigenous chicken found in Imphal Valley of Manipur and is reared in the backyard system mainly for cock fighting. These birds have elongated body with long neck and long legs. Broodiness is usual. Plumage colour is black or brown and pattern is generally patchy in males and solid in females. Cocks generally have shinning bluish black feathers on wings, breast, tail and thighs. Neck, breast and thighs are generally bare, hard and rose red coloured in fighting cocks. Comb is red in colour and is of pea type. Average body weight of an adult cock was 3.01±0.06 kg and that of an adult hen was 2.32±0.09 kg. A Kaunayen hen lays about 35 eggs/annum. Eggs were medium in size with an average of 42.43±.07g. Shell colour was brown. Albumen index, yolk index and haugh units were 0.07±0.01, 0.38±0.01, 76.88±2.35 respectively. Morphologically, Kaunayen look similar to Danki and Aseel breeds but is native to the area (Manipur) which is far apart and geographically isolated from the breeding tract of Danki (Andhra Pradesh) and Aseel (Andhra Pradesh, Orissa and Chhattisgarh). Over the centuries, these have adapted to the local conditions and hence can be classified as a different population of fighter birds.